Antioxidant from Turmeric Fermentation Products (Curcuma longa) by Aspergillus Oryzae - Sulasiyah Sulasiyah; Purbowatiningrum Ria Sarjono; Agustina L. N. Aminin (Jurnal Kimia Sains dan Aplikasi, 2018)
The antioxidant capacity of natural materials can be improved by fermentation. In this study, turmeric rhizome was fermented by Aspergillus oryzae. Fermentation products were obtained with fermentation time of 14, 21 and 28 hours. Furthermore, the fermentation product was extracted using ethanol and determined its antioxidant capacity by DPPH damping method, total phenolate determination and phytochemical screening. The results showed that the antioxidant capacity of fermentation products was higher than without fermentation. Antioxidant activity increased with length of fermentation with the value of antioxidant capacity without fermentation and with incubation for 14, 21, and 28 days respectively of 17.0; 27.3; 33.3; and 34.1 mg quercetin/gram extract. The total phenolate of fermentation products was 261; 324,3; 361; 374.3 mg of gallic acid/gram extract. Ethanol extracts of fermented and non-fermented products all contain entirely positive alkaloids, saponins, flavonoids, tannins, quinones, and steroids.